2008
DOI: 10.1348/026151007x200385
|View full text |Cite
|
Sign up to set email alerts
|

Rotten apple or rotten barrel? Social identity and children's responses to bullying

Abstract: Recent research has suggested that bullying behaviour may be understood as a group process, where those involved act in ways predicted by social identity theory (Ojala & Nesdale, 2004). One relevant phenomenon is the black sheep effect, whereby individuals evaluate deviant members of their in‐group more negatively than that of an out‐group. To examine this process, a study was conducted (N = 60) in which 10‐ and 11‐year‐old children were randomly assigned to a high‐status, peripheral or irrelevant group. They … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 57 publications
2
31
0
6
Order By: Relevance
“…The fourth reason was the importance assigned by numerous researchers to the peer group dynamics as a factor shaping the rejection process among middle school students (Forsyth, 2006;Gini, 2005;Jones, Haslam, York & Ryan, 2008;Salmivalli & Voeten, 2004;Sendyk, 2001;Wentzel, 1998). Research shows that victimisation and exclusion increase on average at school transition (Shell, Gazelle & Faldowski, 2014) because victimisation serves to establish social hierarchies during the formation of peer group and exclusion to maintain it (Pellegrini, 2002).…”
Section: Bullying and Exclusion From Dominant Peer Groupmentioning
confidence: 99%
“…The fourth reason was the importance assigned by numerous researchers to the peer group dynamics as a factor shaping the rejection process among middle school students (Forsyth, 2006;Gini, 2005;Jones, Haslam, York & Ryan, 2008;Salmivalli & Voeten, 2004;Sendyk, 2001;Wentzel, 1998). Research shows that victimisation and exclusion increase on average at school transition (Shell, Gazelle & Faldowski, 2014) because victimisation serves to establish social hierarchies during the formation of peer group and exclusion to maintain it (Pellegrini, 2002).…”
Section: Bullying and Exclusion From Dominant Peer Groupmentioning
confidence: 99%
“…As such, group members are likely to be rewarded for adherence to group norms, or rejected by the group when they fail to adhere to them (Morrison, 2006). Building on this, it was hypothesized (e.g., Jones, Haslam, York, & Ryan, 2008;Jones, Livingstone, & Manstead, 2011Nesdale, 2007) that bullying might be a set of behaviours that is motivated by social identity processes, including levels of ingroup identification, and adherence to group norms. In line with this hypothesis, a number of studies have indicated the role of social identity processes in maintaining bullying.…”
Section: A Social Identity Account Of Bullyingmentioning
confidence: 99%
“…They gave children scenarios to read, and found that children understood that story characters who engaged in bullying would be rejected by a group with an anti-bullying norm, but accepted by a group with a pro-bullying norm. Evidence from Jones et al (2008), using the minimal group paradigm, showed that children encouraged to identify with a perpetrating group in a scenario concluded that one bullying child from that group was deserving of punishment for a bullying incident, whereas third party group members concluded that the whole of the perpetrating group was punishable. Furthermore, Nesdale, Durkin, Maass, Kiesner, and Griffiths (2008) showed, in a minimal group study, that children"s intentions to engage in bullying were greater when they were assigned to a group that had a norm of outgroup-disliking, rather than a norm for outgroup-liking.…”
Section: A Social Identity Account Of Bullyingmentioning
confidence: 99%
“…Encontramos que la mayoría de los implicados, como bullies y como víctimas, fueron chicos (Cerezo y Ato, 2010;Piñero, 2010). La mayor implicación de los chicos en las dinámicas de agresión y victimización se ha relacionado con menor competencia social, normalización de la violencia y habituación al comportamiento agresivo (Avilés, 2006), subrayando también otros trabajos la importancia de la popularidad y las motivaciones de tipo social de los agresores varones (Jones, Haslam, York y Ryan, 2008;Olthof y Gossens, 2008). No se han observado diferencias en los niveles de implicación en las dinámicas agresivas al comparar a estudiantes inmigrantes y españoles, coincidiendo estos datos con estudios anteriores, como los del Defensor del Pueblo (2006), pero contrastando con trabajos que han colocado con mayor frecuencia a los estudiantes inmigrantes en situación de victimización (Funk, 1997; de estructura familiar pueden propiciar un desajuste en los menores que actúe como factor de riesgo frente al desarrollo de conductas agresivas (Dew y Huebner, 1994;Tur-Porcar et al, 2012).…”
Section: Discusión Y Conclusionesunclassified